Principle of lex specialis - Hashim, Majeda; Naeem, Hadi (Journal of Legal Sciences, 2022)
The principle running a distinguished position among the general principles of law in international law ,and because it is  one of the  well- established  principle in the national legal systems in the world ,and this justifies the voluntary approach of the principle as an expression of the will of stste, so the principle was under study by the international law commission in the subject of fragmentation as one of the legal methods linking the rules systems of traditional interntional law to maintain its coherence. Thst the  works of the principle by international judiciary between the various international legal standards are in accordance with the concept of jurisprudence with certain conditions and in view of its distinctive characteristics however ,the application of the principle faces difficulties whose identification is an aspect of the precise definition of the principle.